Determining success factors for effective strategic change: Role of middle managers' strategic involvement - Ukil, Minhajul Islam; Akkas, Md. Ali (Serbian Journal of Management, 2016)
Middle managers are believed to play most crucial part in strategic change that in consequence leads to organizational success. The present study seeks to identify the underlying success factors for effective strategic change and, to investigate the relationship between middle management strategic involvement and effective strategic change. Data were collected following a survey administered among a group of mid-level managers (N=144) serving in twenty different private commercial banks in Bangladesh, and analyzed using various statistical tests including descriptive analysis, Pearson correlation, and simple and multiple regressions in STATA. Results uncovers that factors like relation with top management, strategy, role and skills are essential for effective strategic change. This study also reveals significant relationship between middle management strategic involvement and effective strategic change. Findings of this research suggest that organizations shall involve mid-level managers to formulate and implement strategy since middle mangers work as a bridge between top management and ground level workers.